Plester sariawan efektif dalam mempercepat penyembuhan stomatitis aftosa rekuren dan ulkus traumatikus - Rahmi Amtha; M Marcia; Anggia Irma Aninda (Faculty of Dentistry, Universitas Gadjah Mada, 2017)
Mouth ulcer plaster is effective in accelerating the healing of recurrent aphthous stomatitis and traumatic ulcers. Recurrent aphthous stomatitis (RAS) is one of the most commonly occurring oral diseases. The prevalence of oral ulceration worldwide is 4%, with RAS having the largest proportion (25%). Recurrent aphthous stomatitis is oral ulceration which has a self-limiting disease, but the specific medication to reduce pain caused by lesion is still less varied nowadays. This study aimed to examine the differences in the effectiveness between topical application of hyaluronic acid (HA), mouth ulcer plaster (MUP) and 0.1% triamcinolone acetonide (TA) as a positive control in the healing of RAS and traumatic ulcers (TU). This was a quasi-experimental study by measuring the lesion diameter as well as visual analogue scale (VAS) pre- and post-administration of three types of medication. Kruskal-walis test results show that there are differences in effectiveness (p=0.000) of the three types of medication to cure RAS and TU. There are signicant differences in the reduction of RAS and TU lesion diameter (p = 0.015) and VAS (p = 0.038) with the use of HA and MUP on the 4th day. There is no signicant difference in effectiveness (diameter and VAS) of MUP and TA medication on the fourth day (p = 0.880 and p = 1.000 respectively). There is no signicant difference among HA, MUP and TA on the healing of the lesions on the seventh day (p>0.05). It can be concluded that the effectiveness of MUP is similar to that of topical medications containing corticosteroids in the healing of RAS and traumatic ulcers.ABSTRAKStomatitis aftosa rekuren (SAR) merupakan salah satu penyakit mulut yang paling umum terjadi. Prevalensi ulserasi mulut di seluruh dunia adalah 4%, dengan SAR menempati urutan terbesar yaitu 25%. Stomatitis aftosa rekuren merupakan ulserasi mulut yang memiliki self-limiting disease, namun sediaan obat yang spesifik untuk mengurangi rasa sakit yang ditimbulkan lesi sampai saat ini masih kurang bervariasi. Penelitian ini bertujuan untuk mengetahui perbedaan efektivitas antara aplikasi topikal asam hialuronat (AH), plester sariawan (PS) serta triamcinolone acetonide 0,1% (TA) sebagai kontrol positif dalam menyembuhkan SAR dan ulkus traumatikus (UT). Jenis penelitian eksperimental klinis kuasi dengan mengukur diameter lesi serta skala visual analog (VAS) pra dan paska pemberian tiga jenis obat. Hasil uji Kruskal-walis menunjukkan bahwa terdapat perbedaan efektivitas (p=0,000) ketiga jenis obat terhadap penyembuhan SA dan UT. Terdapat perbedaan bermakna penurunan diameter lesi (p = 0,015) dan VAS (p = 0,038) SAR dan UT dengan penggunaan AH dan PS pada hari ke-4. Tidak ada perbedaan bermakna efektivitas (diameter dan VAS) obat PS dan TA pada hari ke-4 (p = 0,880 dan p = 1,000 secara berurutan). Tidak ada perbedaan bermakna antara masing-masing obat AH, PS dan TA terhadap penyembuhan lesi pada hari ke-7 (p >0,05). Kesimpulan efektivitas PS sama dengan obat topikal yang mengandung kortikosteroid dalam menyembuhkan stomatitis aftosa dan ulkus traumatikus.